Studi Eksplorasi Sistem Drainase Fasilitas Sisi Udara di Bandar Udara: A Systematic Review - Chandra, Putu Wisnu Ardia; Suryan, Viktor; Amalia, Direstu; Sari, Anggi Nidya (Universitas Batanghari Jambi, 2024)
The Airside is a vital area related to aircraft movement. A drainage system needs to be implemented at each airport to support airside safety. This research aims to find out the drainage system at several airports. The exploration study of the drainage system on the air side uses a qualitative method based on a systematic literature review by comparing studies obtained through Google Scholar in the 2015-2024 period. Then, the author analyzes the issues raised using GAP analysis techniques. The sample airports are Juwata Tarakan Airport, Rahadi Oesman Ketapang Airport, Sultan Muhammad Salahuddin Bima Airport, Kualanamu Deli Serdang Airport, and Husein Sastranegara Bandung Airport. This study found that several factors, including structural damage, inefficiency of channel dimensions, instability of retaining walls, lack of rain catchment areas, and accumulated sedimentation, cause the overflow of water that arises when rain occurs. Therefore, it can be concluded that the airport needs to evaluate the effectiveness of channel dimensions using hydrological and hydraulic analysis methods. In addition to evaluation, the drainage system needs to be maintained, which refers to KP 94 of 2015 and KP 326 of 2019. Drainage maintenance activities can be carried out by cleaning sedimentation, vines, grass, and sediment in the channel to save operational costs and increase the channel's life. In addition, overflows on the air side can be minimized, and the safety of flight operations can be guaranteed.